Changes in Research Trends and Topics on Carbon Neutrality Before and After the 2016 Paris Agreement - Insung Hwang; Woojun Jung; Keuntae Cho (IEEE Access, 2025)
Carbon neutrality has become a critical global objective that influences climate governance and shapes research trends, particularly in G20 nations. This study systematically analyzes how academic research on carbon neutrality has evolved in these countries by comparing the periods before and after the 2016 Paris Agreement. A quantitative bibliometric analysis, combined with latent Dirichlet allocation (LDA) topic modeling, was conducted on 2,376 peer-reviewed articles published between 2005 and 2023; these were retrieved from the Web of Science database. The findings indicate a significant increase in research volume and notable thematic shifts following the Paris Agreement, moving from technology-oriented topics towards comprehensive, policy-driven themes such as renewable energy integration, regulatory frameworks, economic incentives, and urban sustainability. Country-specific comparisons highlight various national emphases. China has intensified its research on industrial decarbonization and sustainable economic strategies. The United States has emphasized renewable energy technologies and economic viability. The European Union has focused on urban innovation, regulation, and green finance. Japan has prioritized catalytic processes and industrial efficiency. Finally, South Korea has integrated technological advancements with practical urban applications. These results underscore the need for tailored national policies that leverage economic strengths complemented by intensified international collaboration, including technology transfer and green finance.